Unpacking the optimistic mindset of business students towards entrepreneurship. - Haoran Ma; Ali Junaid Khan; Sana Fayyaz; Waseem Ul Hameed; Habib Ullah (PLoS ONE, 2024)
Entrepreneurial ventures are established in large numbers in China. The success rate of these entrepreneurial ventures is lower than that of new startups. Mismanagement and a lack of creative skills among entrepreneurs are cited as reasons for entrepreneurial failure in China. The current study investigates the impact of entrepreneurial networking and new venture intention on entrepreneurial success in China, with psychological capital and entrepreneurial optimism serving as moderators. 483 responses were collected from business students in China for data analysis. The findings of the study reveal that the impact of entrepreneurial networking and new venture intention on entrepreneurial success in China, with the moderating role of psychological capital and entrepreneurial optimism, is significant. The theoretical framework of this research has novelty as it introduces new moderating relationships of psychological capital and entrepreneurial optimism in the model of entrepreneurial success. Practically, this study has revealed that entrepreneurial success can be achieved with entrepreneurial networking, entrepreneurial optimism, psychological capital, and new venture intention. The directions of this research point out additional gaps in the literature that scholars should discuss in subsequent studies.